Greenhouse Gas and Ozone Radiative Forcing for the RCP8.5 Scenario with the EMAC Chemistry-Climate Model - Gellhorn, Catrin; Langematz, Ulrike; Meul, Stefanie; Ponater, Michael; Kubin, Anne; Abalichin, Janna (2015)
One metric to show the impact of changes in the human and natural emissions of climate active agents on the earth's climate system is the concept of radiative forcing (RF). It quantifies the energy imbalance that occurs when an imposed perturbation, for instance by a change in the mixing ratio of a greenhouse gas (GHG), takes place. There are several ways to calculate the radiative forcing, which differ in the included feedback processes. The instantaneous RF is calculated with fixed atmospheric background conditions to get the net change in the radiative flux ”instantaneously”, while the adjusted RF allows the temperature profile to adjust to a new equilibrium in the stratosphere, with the tropospheric temperature profile remaining unchanged. The goal of this study is to derive the RF of the troposphere due to projected future changes of ozone and GHGs by applying the new sub-model RAD in the ECHAM/MESSy Atmospheric Chemistry (EMAC) model. The instantaneous and adjusted RFs for the GHGs as well as for ozone (tropospheric and stratospheric changes separated) have been calculated. The analyses are based on the reference period 1865 (10 years from a time slice simulation) and the RF is derived for every decade from 1965 (1960–1969) until 2095 (2090–2099). The ozone and GHG concentrations, needed as input for the RF calculations, are taken from a transient simulations of the EMAC chemistry-climate model. The simulations extend from 1960 to 2100, and include forcings by GHGs following the specifications of the RCP8.5 scenario, and by ozone depleting substances following the specification of the adjusted A1 scenario. Sea- surface temperatures and sea-ice concentrations were prescribed from the Max Planck Institute ocean model (MPIOM).